Motivation in elite athletes: a study on what makes a set of female swimmers perform above or under their expected potential - Dahl, K. E. (2012)
What makes some athletes perform at their highest potential level whilst other athletes fail to do so? A good understanding of an athlete`s motivation is critical to a coach designing an appropriate environment and to maximize their athlete`s physical potential. This paper examines how motivation is experienced and expressed by a group of elite athletes within the framework of Self-Determination Theory (SDT). Findings of this investigation indicate that high performance athlete had their needs satisfied and further, show high level of self determined motivation. Consequently, low performing athlete did not have their need satisfied, showed low levels self determined motivation and even indication of amotivation. However, it is not as clear cut because some of the thriving athletes showed signs of non self-determined motivation and low performing athlete showed indication of intrinsic motivation.